Use of Lactobacillus plantarum and Propionibacterium freudenreichii ssp. Shermanii as inoculants in corn silage fermentation - Abdul Rahman, Norafizah (2017)
Bacterial inoculant as feed additives have been shown to be beneficial in silage fermentation in many parts of the world. However, there is still not much evidence of the use of bacterial additives in Malaysia and the impact of using them to produce quality feed for ruminant industry is rarely documented. Thus, this study was conducted to determine the effectiveness of using two bacterial additives for corn silage fermentation in Malaysia. The two bacterial species used in this study were Lactobacillus plantarum (B1) and Propionibacterium freudenreichii (B2). These bacteria were applied singly and as a mixture of both bacteria (B3). Three experiments were conducted where the first experiment was to determine the suitable bacterial growth condition and inoculation size. The preferable growth media for B1 was found to be MRS agar (18-24 hours) while for B2, it was Reinforced Clostridium Difficle Agar (48-56 hours). The wavelength for OD measurement of B1 was 490 nm and 419 nm for B2. Suitable inoculation size for B1 and B2 applied individually was at 1 x 105 cfu/g, while suitable inoculation size for B3 is 0.5 x 105 cfu/g. The second experiment was conducted to determine the effect of B1 and B2 applied singly or as a mixture to the fermentation characteristic and quality of corn silage. The physical characteristic of the silage measured were pH, mould and temperature while the quality measurement included crude protein (CP), dry matter (DM) and fibre content. The fermentation products measured were water soluble carbohydrate (WSC) and fatty acid concentrations (lactic, propionic, acetic and butyric acids). A good silage quality should have a low pH, acetic acid, and butyric acid, but high lactic acid content. Whole corn plant was harvested at dough stage (32 - 37% of dry matter) and cut into 2-3 cm particle size using a forage chopper. Two kilograms of chopped materials were placed on polyethylene sheet and sprayed with 10 ml of prepared bacteria solution. The forage were mixed thoroughly and ensiled in four replicates for each treatment in 4 L laboratory silo. Bacterial combination (B3) ended with the lowest pH (3.33), while the highest was B2 (pH 3.45). The pH of silage treated with bacteria showed a faster reduction compared to untreated silage. The use of L. plantarum alone rapidly reduced pH in the early stages of silage fermentation. Bacterial additives did not reduce mould infection and silage treated with B2 produced higher mould percentage than control (B0). Bacterial treatment did not reduce the fibre content as compared to control. Both bacteria in this research showed low activity on digesting fibre. Bacterial treatments gave a significant effect (p<0.01) on WSC, lactic acid (LA) and acetic acid (AA) while there was no significant effect on propionic acid and butyric acid. Fermentation with L. plantarum alone appeared to produce high LA concentration among all treatments. The LA production was 12 times higher than AA production showing that it promoted the homolactic fermentation to be dominant in the silage. However, when L. plantarum was mixed with P. freudenreichii, the fermentation tended to be dominated by P. freudenreichii. The effect of bacterial additive was observed at 5 different ensiling period (3, 6, 9, 18 and 27 days) and the quality was determined in the third experiment. The time course study in fermentation indicated that the ensilation process was completed at day 6 even without using bacterial additives. This research showed that silage produced with L. plantarum or P. freudenreichii either alone or mixed together produced a desirable silage property but it was not significantly better than control. It was speculated that naturally occurring bacteria was already adequate in the uninoculated corn silage because of the high amount of fermentable sugar in the corn itself which provided the essential source of energy for bacteria to carry out successful preservation during fermentation. Hence, the nutrient qualities of corn silage produced with the addition of the two selected bacteria strains were shown to be the same as uninoculated corn silage.